PENGARUH STRUKTUR KEPEMILIKAN, DIVERSITAS GENDER DEWAN KOMISARIS, DAN VALUE CREATION TERHADAP FINANCIAL DISTRESS - Ghazna Jullab Khorraz; Totok Dewayanto (Diponegoro Journal of Accounting, 2020)
This study aimed to examine the impact of institutional ownership, managerial ownership, foreign ownership, goverment ownership, gender diversity board of commisioner and value creation the posibility of financial distress. This study use leverage as control variable The population in this study includes all companies listed on Bursa Efek Indonesia (BEI) in 2015-2018. The samples conducted by purposive sampling method. Criteria for financial distress company is a company with Altman-Z score under 1,81 in the reporting period. The sample used in this study were manufacturing companies that have availability annual report in 2015-2018. The total sample is 316 companies, which consists of 158 companies financial distress as well as 158 non-financial distress companies with similar industry and accounting reporting period. The analysis technique used is logistic regression.The results of anlysis showed that the variables of institutional ownership, foreign ownership and value creation in a significant negative effect on the possibility of financial distress, while variable managerial ownership, goverment ownership, and gender diversity board of commisioner not significantly affect the financial distress.